Analisis Faktor-Faktor yang Mempengaruhi Utang Luar Negeri dan Pertumbuhan Ekonomi di Indonesia - Elsi Maryani; Zul Azhar; Isra Yeni (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to analyze the influence of the budget deficit, and inflation on Indonesia's foreign debt and analyze the influence of inflation, foreign direct investment and foreign debt on economic growth in Indonesia.This research is classified into descriptive and inductive research. Using annual time series data from 1986-2020. The analytical model used in this study uses a multiple linear equation analysis model using the Ordinary Least Square (OLS) method and simultaneous equation analysis using the Indirect Least Square (ILS) method.The results show that there is a positive and significant effect of the budget deficit variable and there is a negative and significant influence of the inflation variable on Indonesia's foreign debt for the period 1986-2020, and there is a negative and significant influence of the inflation and foreign debt variable on economic growth in Indonesia, while the variable Foreign direct investment has a positive and insignificant effect on economic growth in Indonesia for the period 1986-2020.Based on the results of this study, it is recommended that the government make policies that can reduce the level of foreign debt and the government must carry out new strategies to increase economic growth.